CARBONIC ANHYDRASE AND GLUTATHIONE PEROXIDASE. MOLECULAR PHYLOGENESIS AND PHYSIOLOGICAL IMPORTANCE FOR ENVIRONMENTAL STRESS RESISTANCE - Sattin, Giovanna (Università degli studi di Padova, 2010)
Glutathione peroxidase (GPX, EC 1.11.1.9 and EC 1.11.1.12) and Carbonic anhydrase (CA, EC 4.2.1.1) are two enzymes important for a variety of adaptation/tolerance processes of organisms. CA plays a key role in osmoregulation when GPX is one of the most important enzymes involved in protection of the organism against oxidative damage. In my thesis I studied GPX and CAs from Antarctic teleosts species of Notothenidae and Bathydraconidae (Paper I-II) and CAs from intertidal teleosts (Periophtalmus sobrinus, Gobidae, and Opsanus beta, Batrachoididae (Paper II-III). Firstly, I compared the obtained sequences with those available in database for teleosts and other vertebrates (human, mouse and bird) to reconstruct the molecular phylogeny of two enzyme in teleosts (Paper I-II). Finally, I have investigated the role of CA for the osmoregulation in seawater toadfish (Opsanus beta) exposed to hypersalinity (Paper III). The GenBank database, few sequences of GPX and CAs of temperate teleosts are available and no data are available for Antarctic or intertidal fish were not present. In particular, I choose to study those species because they live in environments with peculiar chemical/physical parameters that influenced, during the evolution, their physiological, morphological and behavioural characteristics. The Antarctic fish (Papers I-II) live in a well delimited geographic zone. The Southern Ocean is comprised from the Antarctic continent to the Polar Front, a curved current continuously encircling Antarctica where cold, northward-flowing Antarctic waters meet and mix with the relatively warmer sub-Antarctic waters. In this limited zone, macro evolutionary events happened, such as radiation of some fauna components. Most of the fish species living in this zone (like nototenioidae) are presents only there. Temperature (-1.9 °C) and salinity (34.8 ppt) are lower than in temperate Oceans (Legg et al. 2009). As a consequence, the oxygen concentration is higher (9 mg l-1 (Meiner et al. 2009)) in these waters because of the ...